2004
DOI: 10.1128/iai.72.11.6191-6196.2004
|View full text |Cite
|
Sign up to set email alerts
|

New Concepts in Antibody-Mediated Immunity

Abstract: After stimulating the development of immunology in the early 20th century, the study of the functional aspects of antibody-mediated immunity (AMI) stagnated in the 1960s because the function of antibodies (Abs) was considered understood and available Ab preparations were limited to polyclonal immune sera. Abs in polyclonal sera are heterogeneous, and the uniqueness of each preparation with respect to specificity and isotype posed formidable problems in achieving consistency, reliability, and reproducibility in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
44
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 97 publications
3
44
0
Order By: Relevance
“…50) and the mouse hepatitis virus (34), two virus models where the Abs help control virus replication in CNS. Of note, sera is known to exert immunoregulatory effects independent from the presence of Ag-specific Abs, such as the Fc receptordependent induction of anti-inflammatory cytokines (51,52). The increased survival of infected wild-type and Mt KO neonatal mice following treatment with sera from naive mice would support this notion (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…50) and the mouse hepatitis virus (34), two virus models where the Abs help control virus replication in CNS. Of note, sera is known to exert immunoregulatory effects independent from the presence of Ag-specific Abs, such as the Fc receptordependent induction of anti-inflammatory cytokines (51,52). The increased survival of infected wild-type and Mt KO neonatal mice following treatment with sera from naive mice would support this notion (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…This hypothesis was supported by several studies demonstrating that Abs can mediate resistance to a variety of intracellular bacterial and fungal pathogens (49,50). Ab-mediated protection has been described in host defense against M. tuberculosis (51), Listeria monocytogenes (52), Candida albicans (53), Histoplasma capsulatum (54), C. neoformans (49,50), and E. chaffeensis (44,55). However, our results also indicate that immune sera and B cells protected SCID mice against body weight loss but did not significantly reduce splenomegaly and bacteria burdens, suggesting that Ab alone cannot control C. burnetii infection.…”
Section: Discussionsupporting
confidence: 59%
“…The finding that purified IgG from immune sera conferred a level of protection similar to immune sera demonstrated that IgG is the protective component in immune sera, suggesting Ab-mediated immunity plays an important role in PI-V-induced protection. This hypothesis was supported by several studies demonstrating that Abs can mediate resistance to a variety of intracellular bacterial and fungal pathogens (49,50). Ab-mediated protection has been described in host defense against M. tuberculosis (51), Listeria monocytogenes (52), Candida albicans (53), Histoplasma capsulatum (54), C. neoformans (49,50), and E. chaffeensis (44,55).…”
Section: Discussionmentioning
confidence: 51%
“…Despite increasing evidence that many specific Abs can interfere with the growth and metabolism of microbes directly (15), little is known about the microbial response to Ab binding. For the human pathogenic fungus C. neoformans, Ab-mediated protection is associated with interference of polysaccharide release and biofilm formation (8,9).…”
Section: Discussionmentioning
confidence: 99%